Penyuluhan Upaya Pencegahan Penyakit Apendisitis Pada Remaja Di Perguruan Islam Modern Amanah-Smp Tahfiz Qur’an - Afina Muharani Syaftriani; Maria Haryanti Butar-butar; Sri Lasmawanti (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
Appendicitis (inflammation of the appendix) is a gastrointestinal disease and surgical disease that often occurs in society, especially among teenagers such as students. Adolescents usually have poor fiber intake patterns, such as not consuming enough vegetables and fruit, which results in functional obstruction of the appendix and increases germ growth. This is what can cause appendicitis. Facing a situation like this, efforts are needed to prevent the occurrence of appendicitis among teenagers. The aim of implementing this community service is to provide education to teenagers regarding efforts to prevent appendicitis. The method used in carrying out this community service is by providing counseling through lectures and providing leaflets containing counseling material at the Amanah Modern Islamic College-Tahfiz Qur'an Middle School with the address Jalan Captain Sumarsono No. 180, Helvetia Village, Medan Sunggal District, Deli Serdang Regency, North Sumatra. The targets for implementing the activities are students at Amanah Modern Islamic College-Tahfiz Qur'an Middle School. The results of this community service have had a positive impact on the parties involved, especially for students at the Amanah Modern Islamic College-Tahfiz Qur'an Middle School. Students can increase their knowledge regarding Efforts to Prevent Appendicitis in Adolescents. Apart from that, students can also improve their skills in preventing appendicitis in teenagers by trying to consume foods that contain fiber such as vegetables and fruit to avoid appendicitis.